2016
DOI: 10.1128/jb.00338-15
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Intramolecular Periplasmic Disulfide Bond in TcpP Protects TcpP and TcpH from Degradation in Vibrio cholerae

Abstract: TcpP and ToxR coordinately regulate transcription of toxT, the master regulator of numerous virulence factors in Vibrio cholerae. TcpP and ToxR are membrane-localized transcription factors, each with a periplasmic domain containing two cysteines. In ToxR, these cysteines form an intramolecular disulfide bond and a cysteine-to-serine substitution affects activity. We determined that the two periplasmic cysteines of TcpP also form an intramolecular disulfide bond. Disruption of this intramolecular disulfide bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Interestingly, the bile salts deoxycholate, chenodeoxycholate, as well as decanoate (Rosenberg et al ., ) 2,2‐ and 4,4‐dipyridle (Rosner et al ., ) activate the E. coli transcription factor Rob by binding to the regulatory domain causing an unspecified conformational change (Rosenberg et al ., ). In V. cholerae TcpP forms homodimeric disulfide bonds, increasing the transcription of ToxT, when exposed to disulfide stress (Morgan et al ., ). The activation of ToxR by bile salts appears to be not simply a transcription factor undergoing a conformational change to become active, but rather an evolutionary adaptation in which the detrimental effects of its signal (i.e., destabilization by detergent like molecules) has been compensated for by the chaperone like function of ToxS, which facilitates ToxR activation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the bile salts deoxycholate, chenodeoxycholate, as well as decanoate (Rosenberg et al ., ) 2,2‐ and 4,4‐dipyridle (Rosner et al ., ) activate the E. coli transcription factor Rob by binding to the regulatory domain causing an unspecified conformational change (Rosenberg et al ., ). In V. cholerae TcpP forms homodimeric disulfide bonds, increasing the transcription of ToxT, when exposed to disulfide stress (Morgan et al ., ). The activation of ToxR by bile salts appears to be not simply a transcription factor undergoing a conformational change to become active, but rather an evolutionary adaptation in which the detrimental effects of its signal (i.e., destabilization by detergent like molecules) has been compensated for by the chaperone like function of ToxS, which facilitates ToxR activation.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this degradation involves different sets of proteases (Almagro‐Moreno et al , ; Teoh et al , ). Notably, ToxR and TcpP can escape degradation with the help of the accessory periplasmic proteins ToxS and TcpH, respectively (Almagro‐Moreno et al , ; Morgan et al , ). Taken together, PdeC, ToxS, and TcpH demonstrate the striking versatility of transmembrane signaling that combines DSB/free thiol switching with proteolytic processing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ToxR and TcpP, which are involved in virulence and porin regulation of V. cholerae, are activated by DSB formation in their C-terminal periplasmic domains (Fengler et al, 2012;Fan et al, 2014). For TcpP, it has been shown that covalent dimerization via an intermolecular DSB results in activation (Yang et al, 2013 Morgan et al, 2015). Taken together, PdeC, ToxS, and TcpH demonstrate the striking versatility of transmembrane signaling that combines DSB/free thiol switching with proteolytic processing.…”
Section: Role Of the Dsba/dsbb System In Redox Control Of Pdec Activitymentioning
confidence: 99%
“…In V. cholerae, ToxR forms a disulfide-linked complex with a related protein, TcpP, that governs transcription of the virulence regulator toxT. ToxR's regulatory role can be bypassed by overexpression of either TcpP or ToxT (35). The V. parahaemolyticus regulator VtrA lacks periplasmic cysteine residues, precluding disulfide bond formation like that required for TcpP-ToxR interaction in V. cholerae; however, as with TcpP, exogenous expression of VtrA overcomes the requirement for toxR, restoring vtrB transcription and T3SS2 protein expression.…”
Section: Discussionmentioning
confidence: 99%